Implementasi Pembelajaran Problem Based Learning Berbantu Mind Mapping Guna Meningkatkan Efektivitas Pembelajaran Mata Pelajaran Ips di Mts Aswaja Tunggangri - Ira Iqlimatul A’yun; Bagus Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was motivated by the large number of students who had difficulty understanding social studies learning and the lack of school facilities. As with the use of projectors, other teachers still alternate, as a result, many teachers still use conventional learning methods. Researchers think that the use of the PBL learning model is helpful Mind Mapping students can be involved in the learning process from analyzing problems to problem solving. The formulation of the problem in this research is 1) How to implement the assisted PBL learning model Mind Mapping on IPS subjects at MTs ASWAJA Tunggangri. 2) How the influence of the PBL learning model helps Mind Mapping on the effectiveness of social studies learning at MTs ASWAJA Tunggangri? with learning objectives. 1) To find out the implementation of the assisted PBL learning model Mind Mapping on the IPS journey point at MTs ASWAJA Tunggangri. 2) To find out the influence of the assisted PBL learning model Mind Mapping on the effectiveness of social studies learning at MTs ASWAJA Tunggangri. The approach used is a quantitative approach, a type of quasi-experimental research with the entire population of class VII MTs ASWAJA Tunggangri. With a research sample of 2 classes, namely experimental VII A and control class VII B, with a sampling technique simple rondom sampling. In collecting data, researchers used tests, questionnaires and documentation with statistical data analysis techniques, namely the independent sample t-test and N-Gain values ​​which were previously tested for normality and homogeneity. Research results 1. In the experimental class with the assisted PBL learning model mind mapping students play more of a role in the learning process from analyzing problems, discussing to problem solving, whereas in the control class using conventional students seem bored in the learning process, so the application of the conventional model is less effective in implementing the learning model. 2. Results show test output Independent sample t-test The effectiveness of student learning with the help of N-Gain percent in the experimental class was 0.6369 in the 56-75 category, so the effectiveness score was considered quite effective, while in the control class it was 0.3554 in the <40 category which was considered ineffective. With the results of the hypothesis test having a sig (2-tailed) value of 0.000. With this sig value 0.000 ≤ 0.05 then H0 rejected and H1 accepted. So there are differences in student learning outcomes between classes that were given behavior and classes that were not given behavior as well as the effectiveness of learning that was determined between the experimental class and the control class.